Contribution of Social Media in Presenting Academic History Content (Case Study on Instagram @historiadotid) - Masyithoh Nurul Haq; Nurzengky Ibrahim; Kurniawati Kurniawati (Eduvest - Journal of Universal Studies, 2025)
This research aims to investigate the contribution of social media, particularly Instagram @historiadotid, in presenting academic history content. Through a case study approach, we analyze how social media is used to introduce and communicate critical and credible historical information to audiences in an engaging and informative manner. Observation and content analysis methods are used to understand the various strategies used by the @historiadotid account in presenting reliable historical content and attracting public attention, especially millennials who are active on social media. The results of this study are expected to provide new insights into the potential of social media as an effective means of history education and help expand the use of social media, especially Instagram, to access historical knowledge for today's generation.